Modified pressure cooker vs. push-and-plug technique in transarterial embolization for brain arteriovenous malformations: a retrospective comparative study - Wang, Haojie; Xie, Bingsen; Xu, Ye; Zhang, Yibin; Yao, Peisen; Lin, YuanXiang; Zheng, Shufa; Kang, Dezhi (Frontiers in Neurology, 2025)
ObjectiveThis study retrospectively analyzed patients with brain arteriovenous malformation (bAVM) treated by transarterial curative embolization using either the modified pressure cooker technique (mPCT) or the conventional push-and-plug technique (PPT). The primary objective was to assess mPCT’s safety and efficacy by comparing occlusion rates and complications with PPT.Materials and methodsData were retrospectively collected from all bAVM patients who underwent transarterial curative embolization at our institution between April 2019 and April 2023. A total of 188 patients were included, with 61 treated using the mPCT and 127 with the PPT. Baseline characteristics, angiographic and clinical outcome, complications and follow-up data were systematically evaluated and analyzed. Lesions were categorized into two groups according to Spetzler–Martin grade (SMG): SMG I-III and SMG IV-V. Furthermore, multivariable logistic regression was performed to identify independent risk factors for incomplete obliteration.ResultsBaseline characteristics were well balanced between the two groups. Immediately after the procedure, the mPCT group achieved a complete obliteration rate of 49.2% compared with 34.6% in the PPT group (p = 0.056). Subgroup analysis demonstrated a markedly higher immediate complete obliteration rate in SMG I-III lesions treated with mPCT (62.5% vs. 40.1%; p = 0.018). Overall complication rates did not differ significantly between groups (19.7% vs. 23.6%; p = 0.543). On multivariable analysis restricted to the mPCT group, nidus size >3 cm was an independent predictor of incomplete obliteration (OR = 14.042, 95% CI: 2.126–92.739; p = 0.006).ConclusionOverall, occlusion rates did not differ significantly between mPCT and PPT, but mPCT achieved higher rates in SMG I–III lesions with comparable complication rates, suggesting potential benefits in selected cases that require confirmation in larger prospective cohorts with longer follow-up.